Karakteristik Sarang Bondol Peking Lonchura punctulata (Linnaeus,1758) di Kawasan Kampus Universitas Andalas - - Fitri; - Rizaldi; Wilson Novarino (Universitas Andalas, 2014)
A study on the nest characteristics of scaly-breasted munia (Lonchura punctulata) located around campus building and forest areas of Andalas University, Padang has been conducted from September 2013 to February 2014 using survey and nest sampling methods. Result of this study showed that the nest of scaly-breasted munia were located from four to six meter from the ground level. Those nest that located around the campus building were significantly higher than the forest area. Nest position in the tree of campus building area were more often found in primary branchs, whereas the nest of forest area were more often in secondary branchs. The nest of scaly-breasted munia were discover in 10 tree species. Shape and morphological size of the nest tended to be different betwen the two locations. Nest of scaly-breasted munia were made of natural materials and did not use find any synthetic material. Grass (Graminae) were the main material used for the nests.Keywords: nest, characteristics, materials, scaly-breasted munia.